2010
DOI: 10.1540/jsmr.46.249
|View full text |Cite
|
Sign up to set email alerts
|

Simple and non-invasive assessment of the accommodation reflex of the proximal stomach

Abstract: Background: Impaired gastric accommodation of the proximal stomach is one of the major pathophysiological mechanisms in functional dyspepsia (FD). However, no useful method exists for the clinical evaluation of this phenomenon. Aim: The aim of the present study was to establish a simple and non-invasive method for evaluating the accommodation reflex of the proximal stomach. Methods: Nine healthy subjects received up to 1,700 mL water (stepwise administration in 100-mL increments) using a nasogastric tube while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…In a previous study, 15–20 US was confirmed to be a useful modality for assessing GAR. Although a sagittal section and maximal diameter was used in an oblique frontal section, 21,22 we selected the cross‐sectional area of the proximal stomach to assess the GAR in the US method.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In a previous study, 15–20 US was confirmed to be a useful modality for assessing GAR. Although a sagittal section and maximal diameter was used in an oblique frontal section, 21,22 we selected the cross‐sectional area of the proximal stomach to assess the GAR in the US method.…”
Section: Discussionmentioning
confidence: 85%
“…To obtain the cross‐sectional area of the proximal stomach, an US probe was positioned and maintained in an intercostal space of the left axilla (Fig. 2), with the spleen and hilum of spleen as the landmarks for the view as described previously 17–20 . The cross‐sectional area of proximal stomach was estimated by tracing its mucosal side with built‐in calipers for 1–2 min after incremental meal ingestion (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study comparing %normal and %SWC with parameters obtained from a 13 C-acetate breath test revealed that the %normal measured in Ch1 of the M-EGG correlated with elimination half-life (T1/2) and lagtime (Tlag). The %SWC as determined by M-EGG from all channels correlated with T1/2, Tlag, and the gastric emptying coefficient, suggesting that %normal and %SWC values indicate gastric emptying through gastric movement and gastric emptying through coordinated movement of the stomach, respectively (18). We did not find a significant difference in %SWC values between the VP-DG and DG groups.…”
Section: Discussionmentioning
confidence: 99%